Validation of the Australian Pelvic Floor Questionnaire in Chinese pregnant and postpartum women. (February 2020) - Hou, Yuqing; Hou, Dan
Abstract: Objectives: To test the psychometric properties of the culturally adapted Chinese version of the self-administered Australian Pelvic Floor Questionnaire (APFQ) in pregnant and postpartum women. Study design: Between November 2018 and December 2018, a total of 316 pregnant women who met the inclusion criteria in an outpatient setting were enrolled. The participants completed the questionnaire during the third trimester and twice after delivery. The test for validity was composed of face/content validity and construct validity. Reliability testing included internal consistency and test-retest reliability. The degree of responsiveness was assessed using effect size (ES) and standardized response mean (SRM). Results: Two hundred and seventy-four women completed all questionnaires. Content validity, missing data did not exceed 4 % for any questions in the Chinese version of the self-administered APFQ. Construct validity, there was statistically significant difference in the symptoms scores of women with and without subjective suffering bothersome symptoms in bladder function, bowel function, prolapse and sexual function during pregnancy and postpartum periods. Reliability, the total Cronbach's alpha coefficients of the questionnaire in pregnancy and postpartum periods were 0.8, 0.9 and 0.9, respectively, and the intraclass correlation coefficient (ICC) of the total questionnaire was 0.8 during the test-retest. Responsiveness, the Chinese version of APFQ can track changes in bladder function domain and bowel function domain for the women with standardized response mean equal to 0.6 and 0.2, respectively. Conclusions: The Chinese version of the self-administered APFQ had satisfactory reliability and validity, and can longitudinally monitor changes in pelvic floor symptoms during pregnancy and postpartum periods.